Turning the Tide in Turbulent Times : Leveraging Trade for Kazakhstan's Development - World Bank (World Bank, Washington, DC, 2017)
Kazakhstan is facing its greatest economic challenge since the global crisis. With oil prices at US$50 per barrel, the country urgently needs to adjust its economic model and find new sources of economic growth. Kazakhstan main export has been crude oil, considered a low-complexity mineral products, which has made the country extremely vulnerable to shocks. For Kazakhstan to reach high income status it will need to move up the value chain and find new sources of growth. However, new opportunities are arising. China's new Silk Road initiative, renewed regional integration efforts through the Eurasian Economic Union, CAREC and WTO accession are opening up new prospects for Kazakhstan to integrate more successfully with the region and the world and to position itself as a key trade and transit corridor between Asia, Europe, and the Middle East. While Kazakhstan outperforms its regional peers in terms of overall business environment, it still ranks poorly in trading across borders. Kazakhstan is embarking on an economic transformation at a time where new global trends are reshaping economic fundamentals. As countries in Asia and Europe enhance their living standards, opportunity costs will matter more than direct transport costs, resulting in increasing opportunities to transport goods from East Asia to Europe.